Causal relationship between obesity, lifestyle factors and risk of benign prostatic hyperplasia: a univariable and multivariable Mendelian randomization study - Yong-Bo Wang; Lan Yang; Yu-Qing Deng; Si-Yu Yan; Li-Sha Luo; Ping Chen; Xian-Tao Zeng (Journal of Translational Medicine, 2022)
Abstract Background Obesity (waist circumference, body mass index (BMI)) and lifestyle factors (dietary habits, smoking, alcohol drinking, Sedentary behavior) have been associated with risk of benign prostatic hyperplasia (BPH) in observational studies, but whether these associations are causal is unclear. Methods We performed a univariable and multivariable Mendelian randomization study to evaluate these associations. Genetic instruments associated with exposures at the genome-wide significance level (P < 5 × 10–8) were selected from corresponding genome-wide associations studies (n = 216,590 to 1,232,091 individuals). Summary-level data for BPH were obtained from the UK Biobank (14,126 cases and 169,762 non-cases) and FinnGen consortium (13,118 cases and 72,799 non-cases). Results from UK Biobank and FinnGen consortium were combined using fixed-effect meta-analysis. Results The combined odds ratios (ORs) of BPH were 1.24 (95% confidence interval (CI), 1.07–1.43, P = 0.0045), 1.08 (95% CI 1.01–1.17, P = 0.0175), 0.94 (95% CI 0.67–1.30, P = 0.6891), 1.29 (95% CI 0.88–1.89, P = 0.1922), 1.23 (95% CI 0.85–1.78, P = 0.2623), and 1.04 (95% CI 0.76–1.42, P = 0.8165) for one standard deviation (SD) increase in waist circumference, BMI, and relative carbohydrate, fat, protein and sugar intake, 1.05 (95% CI 0.92–1.20, P = 0.4581) for one SD increase in prevalence of smoking initiation, 1.10 (95% CI 0.96–1.26, P = 0.1725) and 0.84 (95% CI 0.69–1.02, P = 0.0741) for one SD increase of log-transformed smoking per day and drinks per week, and 1.31 (95% CI 1.08–1.58, P = 0.0051) for one SD increase in sedentary behavior. Genetically predicted waist circumference (OR = 1.26, 95% CI 1.11–1.43, P = 0.0004) and sedentary behavior (OR = 1.14, 95% CI 1.05–1.23, P = 0.0021) were associated with BPH after the adjustment of BMI. Conclusion This study supports independent causal roles of high waist circumference, BMI and sedentary behavior in BPH.